PERAN DAN TANTANGAN PROFESI PENGEMBANG TEKNOLOGI PEMBELAJARAN PADA PEMBELAJARAN ABAD 21 - Bambang Warsita (Balai Besar Guru Penggerak Jawa Timur, 2017)
Objects in the science of instructional technology are instructional and learning. Instructional and learning are experiencing change and tremendous transformation lately, especially at the turn of the millennium leading to the 21st century. Therefore, this condition is a challenge and demand professional role of instructional technology developers (PTP) to provide solutions. This study aims to describe what are the roles and challenges of the profession instructional technology developer in the learning of the 21st century, as well as what products should be produced by PTP in the future. This study uses a descriptive method. Data collection techniques and information through a literature study. The results of this literature review indicate that the future development of instructional technologies should be able to produce products such as; innovative ICT-based learning models, instructional media, and the application of e-learning. Therefore, the role and challenges facing the current PTP, namely: PTP must be creative and innovative to develop cutting-edge learning model appropriate learning paradigm of the 21st century; PTP must work collaboratively with other professionals in a team to produce a product; PTP needs to improve their competencies, they are competency in the area of learning and competency in the area of technology, especially regarding the new learning media; PTP needs to show real work and o er solutions to problems of learning with e-learning applications. Finally PTP products will be awaited and necessary to support the implementation of the learning process in different types, levels and appropriate education pathway applicable curriculum. AbstrakObjek keilmuan teknologi pembelajaran adalah belajar dan pembelajaran. Belajar dan pembelajaran mengalami perubahan dan transformasi yang luar biasa akhir-akhir ini, terutama pada pergantian millennium mengawali abad ke 21. Kondisi ini menjadi tantangan dan menuntut peran profesi Pengembang Teknologi Pembelajaran (PTP) untuk memberikan solusinya. Kajian ini bertujuan untuk mendeskripsikan apa peran dan tantangan profesi pengembang teknologi pembelajaran dalam pembelajaran abad 21, serta produk-produk apa yang harus dihasilkan oleh PTP di masa depan. Kajian ini menggunakan metode deskriptif. Teknik pengumpulan data dan informasinya melalui studi literatur. Hasil kajian literatur ini menunjukkan bahwa ke depan pengembang teknologi pembelajaran harus mampu menghasilkan produk-produk berupa; model pembelajaran inovatif berbasis TIK, media pembelajaran, dan aplikasi e-pembelajaran. Oleh karena itu, peran dan tantangan yang dihadapi PTP saat ini yaitu: PTP harus kreatif dan inovatif mengembangkan model pembelajaran mutakhir yang sesuai paradigma belajar abad 21; PTP harus bekerja sama secara kolaboratif dengan profesi lain dalam suatu tim untuk menghasilkan produk; PTP perlu meningkatkan kompetensinya, yaitu kompetensi bidang pembelajaran dan kompetensi bidang teknologi khususnya mengenai media pembelajaran terbaru; dan PTP perlu menunjukkan karya nyata dan menawarkan solusi-solusi masalah pembelajaran dengan aplikasi e-pembelajaran yang tepat guna. Akhirnya, peran dan produk-produk PTP tersebut ditunggu dan dibutuhkan untuk menunjang terselenggaranya proses pembelajaran di berbagai jenis, jenjang dan jalur pendidikan sesuai kurikulum yang berlaku.